Microvascular inflammation in renal allograft biopsies assessed by endothelial and leukocyte co‐immunostain: a retrospective study on reproducibility and clinical/prognostic correlates. (11th December 2018) - Delsante, Marco; Maggiore, Umberto; Levi, Jonathan; Kleiner, David E.; Jackson, Annette M.; Arend, Lois J.; Hewitt, Stephen M.; Carter‐Monroe, Naima; Bagnasco, Serena M.; Rosenberg, Avi Z.
Summary: The most prominent histologic lesion in antibody‐mediated rejection is microvascular inflammation (MVI); however, its recognition and scoring can be challenging and poorly reproducible between pathologists. We developed a dual immunohistochemical (IHC)‐stain (anti‐CD34/anti‐CD45 for endothelium/leukocytes) as ancillary tool to improve on the semi‐quantitative Banff scores and allow quantification of MVI. We examined the relationship between CD34–CD45 IHC‐based quantitative MVI score (the inflamed peritubular capillary ratio, iptcr) and renal‐graft failure or donor‐specific antibodies (DSA) strength at the time of biopsy. Quantitative iptcr score was significantly associated with renal graft failure (hazard ratio 1.81, per 1 SD‐unit [0.13 points] of iptcr‐increase; P = 0.026) and predicted the presence and strength of DSA (ordinal odds ratio: 2.42; P = 0.005; 75 biopsies/60 kidney transplant recipients; 30 HLA‐ and/or ABO‐incompatible). Next, we assessed inter‐pathologist agreement for ptc score and ptc extent (focal/diffuse) using CD34–CD45 IHC as compared to conventional stain. Compared to conventional stain, CD34–CD45 IHC significantly increased inter‐pathologist agreement on ptc score severity and extent (κ‐coefficient from 0.52–0.80 and 0.46–0.68, respectively, P < 0.001). Our findings show that CD34–CD45 IHC improves reproducibility of MVI scoring and facilitates MVI quantification and introduction of a dual anti‐CD34/CD45 has the potential to improve recognition of MVI ahead of DSA results.